Cutaneous Malignant Melanoma with Testicular Metastases in a Wild Rabbit (Oryctolagus cuniculus) - Jessica Maria Abbate; Simone Palazzolo; Antonio Ieni; Giuseppe Santi Rapisarda; Giovanni Lanteri (Veterinary Sciences, 2023)
Melanocytic skin tumours have been rarely described in pet rabbits, and exposure to UV light in sparsely haired areas has been hypothesised to play a cancerogenic role. Here, we describe a case of cutaneous malignant melanoma arising from the skin of the scrotum in an 8-year-old male wild rabbit, with testicular metastases as an unusual metastatic site for melanoma reported in humans to date. The tumour was nearly 5 cm in size, firm, and highly pigmented, with multifocal superficial ulcerations and large areas of intratumoural necrosis. The adjacent testis was 1.5 cm, multinodular, and black, obscuring tissue morphology. Histologically, the dermis was expanded by an infiltrative, densely cellular neoplasm composed of nests and sheets of polygonal to spindle neoplastic melanocytes, supported by scant fibrovascular stroma. Neoplastic cells showed intermediate N/C ratio, moderate basophilic cytoplasm, often obscured by abundant brownish granular pigment, and eccentric nuclei with prominent nucleoli. Cellular pleomorphism and nuclear atypia were severe, and high mitotic activity was observed. Diffuse dermal lymphovascular invasion was also observed. The testis was delimited by a thin tunica albuginea, and the parenchyma was largely obscured in its morphology by densely packed neoplastic cells. Seminiferous tubules, lined with a thin basement membrane and containing neoplastic and scattered spermatogenic cells, were occasionally observed. Neoplastic cells within the skin and the testis were positive for HMB-45, Melan-A, and S-100. The growing popularity of rabbits as pets allows for a greater ability to accumulate data on the spontaneous occurrence of tumours in these animals. Furthermore, descriptions of the biological aspects of spontaneously occurring tumours may serve to improve current knowledge in animal species and humans in which the same neoplasm may occur.